2017
DOI: 10.1111/iej.12794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic and sonic activation of root canal sealers on the push‐out bond strength and interfacial adaptation to root canal dentine

Abstract: Ultrasonic activation was associated with higher BS values, deeper intratubular penetration and greater interfacial adaptation to root dentine than sonic activation and no activation techniques, AH Plus had higher BS values than MTA Fillapex irrespective of the type of activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 42 publications
5
68
1
2
Order By: Relevance
“…Therefore, the cements were ultrasonically activated for 2 s in the present study. In terms of dentinal tubule penetration, previous studies showed greater dentinal tubule penetration of ultrasonically activated root canal sealers than the current study (Guimarães et al, 2014;Wiesse et al, 2018). Ultrasonic activation did not increase the dentinal tubule penetration of CSCs in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, the cements were ultrasonically activated for 2 s in the present study. In terms of dentinal tubule penetration, previous studies showed greater dentinal tubule penetration of ultrasonically activated root canal sealers than the current study (Guimarães et al, 2014;Wiesse et al, 2018). Ultrasonic activation did not increase the dentinal tubule penetration of CSCs in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…1,2 The quality of obturations is directly related to the material and the technique employed. [2][3][4][5][6] Regarding root canal filling techniques, lateral condensation presents some limitations in irregular, flat, and complex root canal systems. 3 4,6,7,9 Recent studies have demonstrated the presence of gaps and voids after the use of different root canal filling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Regarding root canal filling techniques, lateral condensation presents some limitations in irregular, flat, and complex root canal systems. 3 4,6,7,9 Recent studies have demonstrated the presence of gaps and voids after the use of different root canal filling techniques. 1,3,4,6 In an attempt to overcome these limitations, some authors have proposed the sonic and ultrasonic activation of sealers causing them to penetrate into the canal, promoting a better adaptation between the sealer and the root canal walls.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not enough to show statistically significant difference. Studies have observed that these results are related to its capacity to interact chemically with the collagen network and form covalent bonds between the epoxy rings and the amine groups of the exposed collagen (25). Similarly, AH Plus has been associated with long-term stability and efficient cohesion between molecules, increasing its micromechanical retention to the root dentin.…”
Section: Discussionmentioning
confidence: 99%